Flood mitigation efforts through community empowerment in Medan City, North Sumatera - Ilham Mirzaya Putra; Efi Brata Madya (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2020)
This research aims to provide solutions in flood disaster countermeasure in Medan based on community empowerment. The research method used was descriptive qualitative research with a literature study approach and forum group discussion. Empowerment in this study consisted of aspects of knowledge and appreciation of the environment, as well as community adherence to environmental-related regulations. The results of this study are: 1) Community knowledge about the environment can be improved by socialization activities, socialization activities are the beginning to raise environmental awareness 2) Knowledge is not enough without appreciation, then community assistance activities are carried out by activating tourism, biopori, and utilization waste so that it has economic value; and 3) Enforcement of the law on the environment must be strictly enforced in order to create a deterrent effect for the community in violation.